2018
DOI: 10.1021/acsbiomaterials.7b00996
|View full text |Cite
|
Sign up to set email alerts
|

Novel N–Br Bond-Containing N-Halamine Nanofibers with Antibacterial Activities

Abstract: N-Halamine compounds have attracted great attention because they are recognized as promising antibacterial agents to control microbial contamination; however, most of the research interests were focused on N-halamines that contain N–Cl bond(s) rather than N–Br bond(s). In this contribution, we report the facile fabrication of N–Br bond-containing N-halamine nanofibers using the electrospinning method for antibacterial usages. The as-produced N–Br bond-containing N-halamine nanofibers (i.e., DBDMH/PAN nanofiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 68 publications
3
18
0
Order By: Relevance
“…It was found that the release rate of N -halamine precursor was low even conducting with vigorous agitation, suggesting that the materials inactivate bacteria via contact killing instead of release killing. Thereafter, Bai et al [ 50 ] investigated the antibacterial behavior of the as-prepared N–Br bond-containing N -halamine nanofibers using inhibition zone test, the appearance of the distinct aseptic ring around the samples validated the release killing mode. Then they tested release rate of active bromine dissociated from the N -halamine nanofibers under different conditions.…”
Section: Chemical Structures and Properties Of N -mentioning
confidence: 99%
“…It was found that the release rate of N -halamine precursor was low even conducting with vigorous agitation, suggesting that the materials inactivate bacteria via contact killing instead of release killing. Thereafter, Bai et al [ 50 ] investigated the antibacterial behavior of the as-prepared N–Br bond-containing N -halamine nanofibers using inhibition zone test, the appearance of the distinct aseptic ring around the samples validated the release killing mode. Then they tested release rate of active bromine dissociated from the N -halamine nanofibers under different conditions.…”
Section: Chemical Structures and Properties Of N -mentioning
confidence: 99%
“…At the present scenario, due to toxicity and multidrug resistance developed by the bacteria against conventional antibiotics, much attention has been given to new classes of antimicrobials [16]. The advanced wound dressings are infused with antimicrobials such as honey [17,18], medicinal plant extracts and their bioactive compounds [19,20,21,22], nanoparticles [23,24,25], essential oils [26,27,28], polycatecholamines [29] and cationic polymers [30].…”
Section: Introductionmentioning
confidence: 99%
“…Antibacterial testing was performed using the colony-counting method [45], with Escherichia coli ( E. coli , 8099, a typical Gram-negative bacterium) and Staphylococcus aureus ( S. aureus , ATCC 6538, a typical Gram-positive bacterium) as the two model bacteria. Typically, E. coli and S. aureus were grown overnight at 37 °C in Luria–Bertani (LB) medium, then the bacterial cells were harvested by centrifugation, washed with phosphate-buffered saline, and diluted to concentrations of 1 × 10 6 CFU/mL.…”
Section: Methodsmentioning
confidence: 99%